Pemanfaatan Cacahan Limbah Pelepah Kelapa Sawit sebagai Media Tanam terhadap Pertumbuhan Bibit Kelapa Sawit di Pembibitan Awal - Toto Suryanto (JURNAL CITRA WIDYA EDUKASI, 2018)
This research aims to looked for the alternative of substitute growing medium of top soil that would be match for the growing of oil palm seedling in pre nursery and to get good dose for the growing medium. It came from a mixture of sub soil + piece of midrib for the growth of oil palm seedling in pre nursery. This research was conducted at Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi on January to May, 2018. The experiment was arranged in a completely randomized design with one factor. There are four rates of the mixture midrib growth medium of sub soil + piece of midrib: 100% sub soil (A0), 75% sub soil + 25% piece of midrib (A1), 50% sub soil + 50% piece of midrib (A2), 25% sub soil + 75% piece of midrib (A3). Each treatments were two replications, and each replications consisted of 3 sample plants so the total unit of experiments were 24 plants. Data were analized with analysis of variance with α 5 %, If there is a significant treatment effect, the further analysis using DMRT (Duncan Multiple Range Test). The result showed that the growing medium which came from a mixture of sub soil + piece of midrib could be the substitute alternative of top soil in pre nursery of oil palm. The dose of the best growing medium was 25% sub soil + 75% piece midrib (A3) which could see from the parameters of plant hight, trunk girth, and dry weight plant.